Carnosic Acid Induces Apoptosis and Inhibits Akt/mTOR Signaling in Human Gastric Cancer Cell Lines - Waseem El-Huneidi; Khuloud Bajbouj; Jibran Sualeh Muhammad; Arya Vinod; Jasmin Shafarin; Ghalia Khoder; Mohamed A. Saleh; Jalal Taneera; Eman Abu-Gharbieh (MDPI AG, 2021)
Gastric cancer is among the most common malignancies worldwide. Due to limited availability of therapeutic options, there is a constant need to find new therapies that could target advanced, recurrent, and metastatic gastric cancer. Carnosic acid is a naturally occurring polyphenolic abietane diterpene derived from Rosmarinus officinalis and reported to have numerous pharmacological effects. In this study, the cytotoxicity assay, Annexin V-FITC/PI, caspases 3, 8, and 9, cell cycle analysis, and Western blotting were used to assess the effect of carnosic acid on the growth and survival of human gastric cancer cell lines (AGS and MKN-45). Our findings showed that carnosic acid inhibited human gastric cancer cell proliferation and survival in a dose-dependent manner. Additionally, carnosic acid is found to inhibit the phosphorylation/activation of Akt and mTOR. Moreover, carnosic acid enhanced the cleavage of PARP and downregulated survivin expression, both being known markers of apoptosis. In conclusion, carnosic acid exhibits antitumor activity against human gastric cancer cells via modulating the Akt-mTOR signaling pathway that plays a crucial role in gastric cancer cell proliferation and survival.